Explaining determinants, impact on breastfeeding, and trends over time of prelacteal feeding practice in Indonesia: a mixed methods study - Rahmartani, LD (2022)
Background Prelacteal feeding (PLF) is any feed other than breastmilk given to newborns within the first few days of birth and/or before breastfeeding is established. PLF has been recognised as one of the challenges to optimal breastfeeding, hence the World Health Organisation (WHO) recommends against it unless medically indicated. In Indonesia, breastfeeding practice is gradually improving, yet PLF prevalence is higher than the global average. However, research about PLF from Indonesia is limited. Moreover, existing literature showed that type of PLF varies across settings, but most studies analysed it as a single entity. This thesis aims to explain the determinants, impact on breastfeeding, and trends over time of PLF practice in Indonesia, overall and by different type.